Crystal and molecular structure of 4-Aminobenzohydrazide - Haider, A.; Akhter, Z.; Siddiqi, H.M.; Tiekink, E.R.T. (Kluwer (now part of Springer), 2010)
The molecule of 4-aminobenzohydrazide is essentially planar and geometric parameters conform to literature precedents. Supramolecular N-H center dot center dot center dot O and N-H center dot center dot center dot N interactions combine to link molecules of 4-aminobenzohydrazide into a three-dimensional network. Weaker N-H center dot center dot center dot N and N-H center dot center dot center dot pi interactions consolidate the structure. The compound crystallizes in the monoclinic space group P2(1)/n with a = 5.411 (2) angstrom, b = 14.000(6) angstrom, c = 9.894(4) angstrom, beta = 103.917(7)degrees, and Z = 4.